The role of tag questions in classroom discourse in promoting student engagement. Issue 1 (2nd January 2022) - Parkinson, Jean; Whitty, Lauren
ABSTRACT: In classroom teaching, where teachers front a large class of students, opportunities for students to talk are limited, with much classroom talk by students involving answering teacher questions. This raises the question of how teachers promote student engagement in their lessons. Using a 394, 671-word corpus of recorded teaching in vocational education, this study investigates a discourse feature of classroom discourse, the use of tag questions. Our study compares the use of tag questions in two teaching contexts: teacher-fronted whole-class teaching in the classroom and teaching through interacting with individuals or pairs during skills-teaching in the workshop or construction site. Every tag question (755) in this corpus was analysed for polarity, position in turn, intonation and speech function. The study shows the importance of tag questions in both contexts in involving students in the instructors' on-going explanations both in silent thought and through brief verbal responses or actions. Instructors also use tag questions to focus students' attention, to ensure that students are following their explanations, to involve students in problem-solving, to seek information about students' practical work, to remind them of known information, and to construct them as co-experts who already have some knowledge and judgement related to their vocational field.